A phosphoprotein gene RT-qPCR assay for detecting all lineages of peste des petits ruminants virus - Xu, Jiao; Zhao, Yonggang; Li, Huicong; Wang, Qinghua; Yu, Jiarong; Wang, Yingli; Bao, Jingyue; Wang, Zhiliang (Frontiers in Microbiology, 2025)
Peste des petits ruminants (PPR) is a highly contagious disease caused by peste des petits ruminants virus (PPRV). PPRV is classified into four lineages based on the nucleocapsid (N) or fusion (F) genes. We established a TaqMan quantitative real-time reverse transcription polymerase chain reaction (RT-qPCR) assay using a pair of primers and a probe based on the phosphoprotein (P) gene. The assay was assessed for its sensitivity, specificity, and repeatability in the detection of field samples and was compared with the standard detection method. The developed method could detect all lineages of PPRV, with a sensitivity of four copies/μL for lineage II to IV and 40 copies/μL for lineage I. The results of the specificity test indicated that only the different lineages of PPRV could be detected using the developed method, with no cross-reaction observed with other viruses. The coefficients of variation for both intra-assay and inter-assay repeatability tests were all below 1.50%, demonstrating good repeatability. The detection of field samples, including PPRV-positive and PPRV-negative samples, indicated that all samples were detected correctly, showing a high concordance with the standard detection method. The developed method could detect PPRV with a lower cycle threshold value compared to the previously established N gene-based method, especially for weakly positive samples. This RT-qPCR assay provides a valuable tool to facilitate targeted surveillance and rapid differential diagnosis in regions with an active circulation of PPRV, enabling timely epidemiological investigations and strain-specific identification.